Pesan Gizi Seimbang “Isi Piringku” untuk Mencegah Stunting melalui Media Modul Emo Demo - Rohmawati, Ninna; Antika, Ruli Bahyu; Rachmawati, Septi Nur; Hermilasari, Rista Dwi (UNEJ e-Proceeding, 2023)
Background: The reduction of stunting by 14% is one of the national targets which refers to the National Action Plan to Accelerate the Reduction of Stunting (RAN PASTI). The percentage of stunted babies in Bataan Village was 16.36%. This percentage exceeds the stunting reduction target percentage. This service activity aims to help prevent stunting in Bataan Village, Tenggarang District, Bondowoso Regency by increasing mother's knowledge and creativity regarding children's balanced nutritional needs according to their age based on my plate guidelines. Method: Emotional Demonstration (Emo-Demo) to improve eating patterns through the contents of my plate and continued with the cooking class as a form of implementation. Results: There is a difference in the pre-test and post-test results from the effects of emo-demo activities, namely 32% to 84%. In the cooking class activity, the value of mother's creativity is 91.25%. Conclusion: Mother's knowledge about a balanced nutritional diet increased after education was carried out using the emo-demo method and the mother's creativity in serving food according to the guidelines for the contents of my plate also reached the predetermined targets.Keywords: balanced nutrition, fill my plate, stunting, emo demo.